Pig rennet in making Farindola ewe cheese - Di Giacomo, Franco; Del Signore, Antonella; Giaccio, Mario (Progress in Nutrition, 2014)
Samples of ewe cheese produced with pig rennet in the Farindola area (Abruzzo, Italy) were compared with samples of ewe cheese produced with calf rennet using the same methods of processing and ripening as the Farindola cheese. To distinguish the samples chemical parameters (18 amino acids and 12 fatty acids) were chosen. In addition a taste analysis was carried out by a Panel of tasting experts. All of the data thereby obtained was analysed statistically through discriminate analysis. Both the analytical data and the taste expert Panel results show a net differentiation between the cheeses produced with the two different types of rennet. The Panel Test found that the ewe cheese made with calf rennet is systematically more spicy (“piccante” flavour) and bitter than the Farindola cheese made with pig rennet, whereas this latter is always sweeter and never bitter.